The Relationship Between Pre-Pregnancy BMI and Stunting Incidence at Soasio Community Health Centre - Suhaimi Agus; Tut Rayani Aksohini Wijayanti (Calory Journal Medical Laboratory Journal, 2025)
Stunting, a major public health issue, is often caused by prolonged nutritional deficiencies during early life. Research shows that maternal nutritional status before conception plays a crucial role in child growth outcomes, but this phase is often overlooked in stunting prevention. The pre-pregnancy body mass index (BMI) is a key indicator of maternal nutrition and may influence a child's linear growth. This study aimed to explore the relationship between maternal pre-pregnancy BMI and stunting in children under five years old in the Soasio Primary Health Center, Tidore Islands City. A cross-sectional analytical observational study was conducted with 50 mother-child pairs selected via total sampling. Maternal pre-pregnancy BMI was obtained from health records, while child stunting was assessed using height-for-age or length-for-age Z-scores based on WHO growth standards. Data were analyzed using univariate analysis, Chi-square tests, and logistic regression. The results revealed a significant correlation between maternal pre-pregnancy BMI and child stunting. Children born to underweight mothers were more likely to experience stunting compared to those born to mothers with a normal BMI. No significant correlation was found between overweight or obesity and stunting. The study concludes that maternal undernutrition before pregnancy is strongly linked to stunting and highlights the need for better nutritional screening and interventions for women of reproductive age.